1997
DOI: 10.1016/s0092-8674(00)80489-4
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Dimeric Kinesin and Implications for Microtubule-Dependent Motility

Abstract: The dimeric form of the kinesin motor and neck domain from rat brain with bound ADP has been solved by X-ray crystallography. The two heads of the dimer are connected via a coiled-coil alpha-helical interaction of their necks. They are broadly similar to one another; differences are most apparent in the head-neck junction and in a moderate reorientation of the neck helices in order to adopt to the coiled-coil conformation. The heads show a rotational symmetry (approximately 120 degrees) about an axis close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
398
2
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(419 citation statements)
references
References 49 publications
13
398
2
6
Order By: Relevance
“…A volume of protein density above the left one-half of the bound head that remains unfilled (Figure 6c) is essentially where the tethered head should be positioned to agree with the dimeric kinesin crystal structure (Kozielski et al, 1997), with the attached head corresponding to head B. Although the map has insufficient density at high radius to accommodate all of head A, probably because of disorder, a second copy of the monomer crystal structure (Figure 6, pink), in an orientation close to that of head A in the crystal structure, readily accounted for the extra density.…”
Section: Fitting the Atomic Coordinates Into Em Density Mapsmentioning
confidence: 83%
See 2 more Smart Citations
“…A volume of protein density above the left one-half of the bound head that remains unfilled (Figure 6c) is essentially where the tethered head should be positioned to agree with the dimeric kinesin crystal structure (Kozielski et al, 1997), with the attached head corresponding to head B. Although the map has insufficient density at high radius to accommodate all of head A, probably because of disorder, a second copy of the monomer crystal structure (Figure 6, pink), in an orientation close to that of head A in the crystal structure, readily accounted for the extra density.…”
Section: Fitting the Atomic Coordinates Into Em Density Mapsmentioning
confidence: 83%
“…Monomeric and dimeric (Kozielski et al, 1997) rat kinesin constructs revealed two additional ␤ strands (␤9 and ␤10) at the C terminus, which are thought to be important for determining the directionality, and an ␣ helix (␣7) that forms a coiled coil in the dimer structure. In crystals of dimeric kinesin two motor domains are asymmetrically related to each other by an ϳ120°rotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that all kinesin molecules in solution within the flow cell attach to the glass surfaces, the kinesin surface density from the 4 µM kinesin solution is estimated to be 108,000 molecules per 1 µm 2 . This is well beyond the saturation limit determined by the size of a single kinesin motor head because it corresponds to one kinesin molecule in an area of ~3 nm × 3 nm which is smaller than the size of a kinesin motor head (~8 nm in diameter) (Kozielski et al, 1997). In order to characterize the general aspect of the motility, we observed microtubules gliding on a region of the coverslip (area: ~50 µm × 50 µm) away from the glass wire (Supplementary Movie, SM12).…”
Section: Motility Assaymentioning
confidence: 87%
“…(41) Although the neck linker was disordered in the first crystal structure of a kinesin motor, (42) presumably due to its mobility in the crystal lattice, subsequent crystal structures show a visible neck linker consisting of two b-strands that interact with other b-strands of the motor domain. (41,43) The mobile or undocked conformation of the neck linker is thought to alternate with docking against the motor core. Undocking of the neck linker would not only potentially enable the two heads of dimeric conventional kinesin to reach between two adjacent binding sites along the microtubule, but could also amplify a small movement of the motor core, producing a power stroke.…”
Section: Motor Mechanical Elementsmentioning
confidence: 99%